2014
DOI: 10.1080/10286020.2014.896342
|View full text |Cite
|
Sign up to set email alerts
|

A new 2-(2-phenylethyl)chromone derivative in Chinese agarwood ‘Qi-Nan’ from Aquilaria sinensis

Abstract: Phytochemical analysis of the high quality Chinese agarwood 'Qi-Nan' originating from Aquilaria sinensis (Lour.) Glig led to the isolation of a new 2-(2-phenylethyl)chromone derivative, qinanones G (1), and four known 2-(2-phenylethyl)chromones (2-5). Their structures were elucidated by spectroscopic techniques (UV, IR, 1D and 2D NMR) and MS analyses. The NMR data of chromones 1-3 were first reported, and chromones 2 and 3 showed weak inhibitory activity against acetylcholinesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…It has been reported that 54 2-(2-phenylethyl)chromones have been isolated from various Aquilaria species [ 4 , 5 ]. In recent years, 35 new 2-(2-phenylethyl)chromones, including 13 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones, have been identified in differing qualities of agarwood products [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Among 89 2-(2-phenylethyl)chromones, 33 highly oxidized chromones appear to be unique to agarwood and are not found in healthy Aquilaria specimens [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 54 2-(2-phenylethyl)chromones have been isolated from various Aquilaria species [ 4 , 5 ]. In recent years, 35 new 2-(2-phenylethyl)chromones, including 13 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones, have been identified in differing qualities of agarwood products [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Among 89 2-(2-phenylethyl)chromones, 33 highly oxidized chromones appear to be unique to agarwood and are not found in healthy Aquilaria specimens [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, feruloyl amides, nucleosides, and lignins have been extensively reported as being involved in plant defenses [25][26][27][28]. The identification of 2-(2-phenylethyl)chromones (1)(2)(3)(4)(5), feruloyl amides (6-8), nucleosides (9)(10)(11)(12)(13)(14), and (+)-syringaresinol (15) would be useful for further exploring the mechanism of agarwood formation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, feruloyl amides, nucleosides, and lignins have been extensively reported as being involved in plant defenses [25][26][27][28]. The identification of 2-(2-phenylethyl)chromones (1)(2)(3)(4)(5), feruloyl amides (6)(7)(8), nucleosides (9)(10)(11)(12)(13)(14), and (+)-syringaresinol (15) would be useful for further exploring the mechanism of agarwood formation. [13], N-trans-feruloyltyramine (6) [14], N-trans-feruloyloctopamine (7) [14], N-cis-feruloyltyramine (8) [14], N 6 -methyladenosine (9) [15], adenosine (10) [16], 2'-deoxy-D-adenosine (11) [16], thymidine (12) [17], 2'-deoxyuridine (13) [17], uridine (14) It is well known that biotic and abiotic stresses could adversely affect plant growth and subsequently cause the production of specific secondary metabolites for plant defense.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwood is a well-known as incense in the oriental region such as in Taiwan, Thailand and China used as a sedative, analgesic, and digestive agent in traditional medicine. Flavonoid glycoside, volatile oil, benzenoid, sesquiterpenes and chromone derivatives were isolated and identified from the seed, leaves or stem of these plants [2][3][4][5][6][7][8][9][10]. Phytochemical constituents obtained from the agarwood including apigenin-7, 4'-dimethylether, genkwanin, quercetin, kaemperfol and 5, 6, 7, 8-tetrahydro-2-(2-phenylethtl) chromes with different pharmacological activities [8,11,12].…”
Section: Introductionmentioning
confidence: 99%